An Adequate Pharmaceutical Quality System for Personalized Preparation - Marta Uriel; Diego Marro; Carlota Gómez Rincón (MDPI AG, 2023)
The pharmacy compounding of personalized preparations has evolved a great deal, and with it, the way of working and the legal requirements have also evolved. An adequate pharmaceutical quality system for personalized preparations presents fundamental differences with respect to the system designed for industrial medicines since the size, complexity, and characteristics of the activity of the manufacturing laboratory and the applications and uses of the manufactured medicines must be taken into account. Legislation must advance and adapt to the needs of personalized preparations, filling the deficiencies currently found in this field. The limitations of personalized preparation in its pharmaceutical quality system are analysed and a method based on a proficiency testing program specially designed to overcome these limitations is proposed: the Personalized Preparation Quality Assurance Program (PACMI). This method makes it possible to expand the samples and destructive tests, and dedicate more resources, facilities, and equipment. It allows for more in-depth knowledge of the product and the processes used, and for proposed improvements that increase the overall quality for improved patient health. PACMI introduces tools used in risk management in order to guarantee the quality of an essentially heterogeneous service: personalized preparation.